How did Paggadde-gadde Maintain its Business? An Ethnography Study Before and During Pandemic of Covid-19 - Andi Sri Wahyuni; Astuti Astuti; Rizky Utami; Nur Asni Safitri; Andi Nurhalizah; Nurul Hidjrah Hairuddin (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2021)
The arrival of the Covid 19 Virus in Indonesia, which is recognized as a national disaster by the government, destroys the economic sector from micro to macro. On the bottom line, small entrepreneurs such as paggadde-gadde were significantly affected among other types of businesses. This study seeks to reveal the culture in the life of a paggadde-gadde in Makassar in an effort to maintain his small business, before and during the pandemic occurs in 2020. The research method used is ethnography, by taking twelve steps of step-by-step research formulated by Spradley (1979). Ethnographic records and analysis results from this study reveal the strategy taken before the pandemic is to provide customers with ease of transactions with loan goods when the customer, who is a neighbor of paggadde-gadde himself, is in financial trouble. However, during a pandemic, another strategy is carried out by not providing loans for a while so that the current asset turnover ratio remains stable. This research can then be used as a reference for other paggadde-gadde in Makassar in particular, and similar home entrepreneurs in general. The results of the research can also be used as a reference for city governments in formulating policies related to regulations involving small businesses such as paggade-gadde businesses.